A Rabbit Corneal Endothelial Dysfunction Model Using Endothelial-Mesenchymal Transformed Cells. Issue 1 (December 2018) - Yamashita, Kazuya; Hatou, Shin; Inagaki, Emi; Higa, Kazunari; Tsubota, Kazuo; Shimmura, Shigeto
Abstract Unlike humans, rabbit corneal endothelial wounds are known to spontaneously heal. The current study was aimed to develop a new rabbit bullous keratopathy model using corneal endothelial cells that were induced to undergo endothelial-mesenchymal transformation (EMT). EMT was induced in rabbit corneal endothelial cells (RCECs) by culturing with TGFβ and basic FGF Supplemented Medium. The corneal endothelia in recipient rabbits were mechanically scraped from the corneal endothelial surface inside an 8 mm mark. Then, a suspension of EMT-induced RCECs (EMT-RCECs) was injected into the anterior chamber. Eyes injected with freshly isolated RCECs (Fresh RCECs group) and eyes that were scraped without injection of cells (Scrape group) were used as controls. Immediately following operation, subepithelial and stromal edema was observed with increased central corneal thickness and corneal opacity in all groups. In the EMT-RCECs group, bullous keratopathy persisted for 42 days up to the end of the study. In the Fresh-RCECs and Scrape groups, corneal transparency and thickness recovered by 7 days after treatment and was maintained up to 42 days. The activated fibroblast marker, α-SMA, was observed spanning from corneal endothelium to corneal stroma in the EMT-RCECs group. Interestingly, α-SMA was upregulated in the Scrape-group as well. In all groups, there was no damage to other intraocular structures, and intraocular pressure was normal throughout the observation period. Transplanting a fresh donor cornea effectively treated corneal edema due to bullous keratopathy. This model is a promising tool for pre-clinical trials in the development of new therapies against corneal endothelial dysfunction.